Determinación de la composición físico - química del lactosuero producido en las empresas lácteas (Lácteos Verito, Prolasfe, Prolad´s). - Guamba Caizaluisa, Andrés Sebastian (2021)
Whey is a by-product of cheese production and is known to be a liquid that contains high nutritional and protein content. Unfortunately in Ecuador, due to the lack of knowledge of small and medium producers, it is a liquid that is discarded in most cases generating a serious environmental contamination, or destined mainly for animal feed and its use in the industry is prohibited in Ecuador. In order for the whey to be used in a suitable way, samples were taken from different dairy companies (Prolad's, Prolasfe, Lácteos Verito), which were subjected to physical-chemical and microbiological analysis. Based on the parameters established by NTE INEN 2495:2011. It is clear that a large number of by-products can be generated from whey based on the liquid mentioned above. It should be emphasized that in order to obtain an excellent whey that can be reused for further processing, it is necessary to work together from the reception of the milk to the storage of the whey.